(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Neural networks are one of the areas of research in the field of artistic intelligence, based on attempts to reproduce the human nervous system. At the same time, it allows you to simulate the work of the human brain, creating the opportunity to study and correct errors of the nervous system.In this article, the issues of neural network modeling are considered on the example of automatic processing of aeronautical data.